To the definition of „anti-Ukrainian activities” - Савойська, С. В. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science", 1970)
The article deals with anti-Ukrainian activities hostile to the Ukrainian people and the Ukrainian state, both internal and external forces. Reported that the anti-Ukrainian activities has ancient roots and history, which started in the era of the Lithuanian-Polish state when the Ukrainian lands were seized by the Poles, and the dawn of Russian-Ukrainian relations, when the pro-Moscow policies are configured and some officials in defending the interests of Ukraine, which continues now.